Mechanical injury polarizes skin dendritic cells to elicit a Th2 response by inducing cutaneous TSLP expression - Oyoshi, Michiko K. (2010)
Atopic dermatitis (AD) is characterized by intense scratching and a Th2 dominated systemic and local immune response to cutaneously introduced antigens. Because scratching inflicts mechanical injury to the skin, we examined the effect of mechanical injury inflicted by tape stripping on the capacity of skin dendritic cells (DCs) to polarize T cells towards a Th2 phenotype. DCs isolated from skin 6 hrs after tape stripping elicited significantly higher production of IL-4 and IL-13, and significantly lower production of interferon-γ (IFN-γ) by OVA stimulated CD4(+) DO.11.10 cells, than DCs isolated from unmanipulated skin, and expressed significantly more mRNA for the Th2 skewing molecules IL-10 and the Notch ligands Jagged1 and Jagged2, but significantly less mRNA for the Th1 skewing cytokine IL-12. CD11c(+)FITC(+) cells isolated from draining lymph nodes (DLN) of shaved and tape stripped mouse skin 24 hrs after painting with FITC polarized T cells towards Th2 significantly more than CD11c(+)FITC(+) cells isolated from DLN of shaved non tape stripped skin, and expressed significantly more IL-10, Jagged1 and Jagged2 mRNA, but significantly less IL-12 mRNA. Tape stripping significantly increased TSLP levels in the skin. Studies in TSLPR(−/−) mice demonstrated that TSLP played an essential role in the Th2 polarization effect of tape stripping on skin DCs. These results suggest that mechanical injury inflicted by scratching in patients with AD polarizes skin DCs to elicit a Th2 response by upregulating local expression of TSLP.